The equation that represents the situation is:
9 + 3x = 6(x - 3)
The value of x is x = 9
Let the number be represented by x
Triple the number = 3x
9 added to the number that is produced by tripling the number x = 9 + 3x
3 less than x = x - 3
6 times the number that is 3 less than x = 6(x - 3)
Therefore, the equation that illustrates the situation is:
9 + 3x = 6(x - 3)
Solve for x in the equation above
9 + 3x = 6x - 18
6x - 3x = 9 + 18
3x = 27
Divide both sides by 3
3x/3 = 27/3
x = 9
Learn more on linear equations here: https://brainly.com/question/14323743